Educação e desenvolvimento natural em Rousseau e Dewey - Wendt, Cristiano Eduardo (2011)
This study seeks to investigate the idea of natural development in the pieces Émile, or On Education, by the Swiss philosopher Jean-Jacques Rousseau, and Democracy and Education, by the American thinker John Dewey. More precisely, it seeks to reconstruct the critique that Dewey does in relation to Rousseau in the ninth chapter of his piece, aiming to show the partial and unfounded character of the American pragmatist s thinking, above all for not considering the normative aspect subjacent to the concept of nature. Therefore, what makes us discuss about this topic is the problem brought up by Dewey, who inquires, in the rousseuan thinking, the identification of the nature concept with the concept of God. According to his objection, the action of the educator would be ineffective in the process of natural development of the child, taking into account that the aptitudes and trends would be inherent to the subjects, afforded by a God of a transcendent and good figure, and they would develop independently of the use they were given. According to such thinking, the physical and social environment and the educator would have a little and unexpressive role in that process. In order to verify the coherence of this affirmation by Dewey, we looked through the pages of Émile for some indications which corroborate that issue. In a special form, our investigation also analyses Books I and II, in which Rousseau shows the age of the nature and in which lies the seed that germinates Dewey s critique. In relation to the natural education, it stems from the nature and the contact with things, seeking, in this phase, to strengthen the body and refine the senses of the child, preparing him/ her to get to the reasoning age and go on in the formation of his/ her character. So as to find a possible response to such matter, we firstly presented Rousseau s thinking and pedagogical positioning; secondly, we interpreted it with focus on Dewey s thinking. Eventually, we tried to refute Dewey s objection, based on the Genevan s writing, above all, in its concept of liberty